2012
DOI: 10.1093/eurjhf/hfs003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognosis of heart failure with preserved ejection fraction and elevated N‐terminal pro brain natriuretic peptide: a 10‐year analysis from the Copenhagen Hospital Heart Failure Study

Abstract: AimsThe aim of this study was to assess the epidemiological features and prognosis of heart failure with preserved ejection fraction (HFPEF) and to compare these findings with those from patients with reduced ejection fraction. Furthermore the effects of N-terminal pro brain natriuretic peptide (NT-proBNP) requirement in the heart failure diagnosis were assessed by repeating the analyses in the subgroup of patients with elevated NT-proBNP. Methods and resultsIn 1844 patients admitted, a clinical diagnosis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
4
22
1
1
Order By: Relevance
“…Outcomes in RELAX were worse relative to prior HFpEF trials when the more sensitive NT-proBNP assay was required for diagnosis 59 , possibly because this may indicate that the patient's shortness of breath is more likely attributed to heart failure 62 . Other circulating biomarkers have been used to diagnose HFpEF, including procollagen, inflammatory factors (interleukins 6 and 8 and TNFα), matrix metalloproteinase, triiodothyronine, heart-type fatty acid binding proteins, troponin T, and carbohydrate antigen-125 5 .…”
Section: Other Promising Therapeutic Agentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Outcomes in RELAX were worse relative to prior HFpEF trials when the more sensitive NT-proBNP assay was required for diagnosis 59 , possibly because this may indicate that the patient's shortness of breath is more likely attributed to heart failure 62 . Other circulating biomarkers have been used to diagnose HFpEF, including procollagen, inflammatory factors (interleukins 6 and 8 and TNFα), matrix metalloproteinase, triiodothyronine, heart-type fatty acid binding proteins, troponin T, and carbohydrate antigen-125 5 .…”
Section: Other Promising Therapeutic Agentsmentioning
confidence: 87%
“…Compared with HFrEF, HFpEF patients are classically more likely to be older, hypertensive females 62 . A retrospective study of new-onset HF in Framingham participants between 1981 and 2008 showed that approximately 50% were classified as HFpEF.…”
Section: Other Promising Therapeutic Agentsmentioning
confidence: 99%
“…18 Another study conducted in Denmark showed that using a heart failure diagnosis requiring elevated NT‐proBNP reduces the prevalence of heart failure with preserved ejection fraction and results in a survival rate similar to that of heart failure with reduced ejection fraction; the finding supported the use of NT‐proBNP for the selection of high‐risk patients having heart failure with preserved ejection fraction in future interventional clinical trials. 19 In 1 recent study, NT‐proBNP also had strong associations with left ventricular systolic dysfunction, 20 even in patients without clinical heart failure; the study evaluated the cross‐sectional associations of NT‐proBNP with cardiac structural and functional abnormalities in patients with CKD (n=3232). NT‐proBNP significantly reclassified participants' likelihood of having left ventricular systolic dysfunction (net reclassification improvement 0.28, 95% CI: 0.27 to 0.30; P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to appropriate identification of patients with HFpEF for clinical trials. Plasma brain natriuretic peptide (BNP) levels are diagnostically helpful because elevated levels not only increase the likelihood that patients have HFpEF but also identify a higher-risk group of patients with HFpEF [13,14]. E/e 0 (the relationship between peak early transmitral ventricular filling velocity and early diastolic tissue Doppler velocity) can help estimate left ventricular filling pressures but can often be abnormal in older patients.…”
Section: Heart Failure and Preserved Ejection Fractionmentioning
confidence: 99%